2008
DOI: 10.1007/s11999-008-0623-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell and Nucleus Pulposus Cell Coculture Modulates Cell Profile

Abstract: Spontaneous cell fusion can occur in cocultured stem cells. We examined whether telomerase activity change and cell fusion occurred in mesenchymal stem cell (MSC) and nucleus pulposus cell (NPC) coculture. MSCs and NPCs were labeled with PKH26 and PKH67 dyes and cocultured at a 50:50 ratio. An equal number of MSCs or NPCs were used as the control. After 14 days, cells were evaluated by cell growth, telomerase activity, quantitative reverse transcriptase-polymerase chain reaction (RT-PCR), immunohistochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
(74 reference statements)
2
15
0
1
Order By: Relevance
“…Following transfection of the nucleus pulposus with the telomerase gene, the percentage of senescent cells to the total nucleus pulposus cells was 3-30% (following telomerase gene transfection) and 4-64% (control group). In addition, the generation of extracellular matrix products, such as collagen, were significantly increased within 120 days and the notable difference was identified at day 21 with a yield that was 7.2 times as high as the control group (14,15). In the present study, the expression levels of chondroitin sulfate and type II collagen in the nucleus pulposus were also significantly lower in the experimental group compared with those in the control group.…”
Section: Discussionsupporting
confidence: 46%
“…Following transfection of the nucleus pulposus with the telomerase gene, the percentage of senescent cells to the total nucleus pulposus cells was 3-30% (following telomerase gene transfection) and 4-64% (control group). In addition, the generation of extracellular matrix products, such as collagen, were significantly increased within 120 days and the notable difference was identified at day 21 with a yield that was 7.2 times as high as the control group (14,15). In the present study, the expression levels of chondroitin sulfate and type II collagen in the nucleus pulposus were also significantly lower in the experimental group compared with those in the control group.…”
Section: Discussionsupporting
confidence: 46%
“…In rabbit culture, PKH26 (red) and PKH67 (green) lipophilic dyes were used. Subsequent to a two-week incubation period on alginate beads 42% of the cells were double-stained (4). A flow cytometric analysis revealed that the exchange of dyes between rabbit NPCs and MSCs is balanced and the cytometric diagram was less asymmetrical (in relation to a 45˚ axis) than our diagram, nevertheless, it is probable that the MSCs secreted more PKH26 due to fewer PHK67-stained NPCs observed (4).…”
Section: Discussionmentioning
confidence: 67%
“…Lipophilic dye exchange has been studied in rabbit and human NPCs and MSC co-culture systems (4,10). In rabbit culture, PKH26 (red) and PKH67 (green) lipophilic dyes were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs can activate NP cells by paracrine stimulation, cell-cell contact or exchange of membrane components [93,94]. Furthermore, anti-inflammatory and immunemodulating activity has been attributed to MSCs [95,96].…”
Section: Accepted Manuscriptmentioning
confidence: 99%